2017
DOI: 10.1158/0008-5472.can-16-3453
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Expression in Head and Neck Squamous Cell Carcinomas Derives Primarily from Functionally Anergic CD4+ TILs in the Presence of PD-L1+ TAMs

Abstract: Oral tongue squamous cell carcinoma (OTSCC) is the most common oral cavity tumor. In this study, we examined the basis for the activity of PD-1-based immune checkpoint therapy that is being explored widely in head and neck cancers. Using multispectral imaging, we systematically investigated the OTSCC tumor microenvironment (TME) by evaluating the frequency of PD-1 expression in CD8+, CD4+ and FoxP3+ tumor-infiltrating lymphocytes (TIL). We also defined the cellular sources of PD-L1 to evaluate the utility of P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 25 publications
5
81
3
Order By: Relevance
“…In contrast to the expression of PD‐L1 in cancer cells of oral squamous cell carcinoma, in our study, PD‐L1 was negative in the oral epithelium of both healthy control and dysplasia samples. In the lamina propria, PD‐L1 was expressed mainly in dysplastic samples and only rarely in controls.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In contrast to the expression of PD‐L1 in cancer cells of oral squamous cell carcinoma, in our study, PD‐L1 was negative in the oral epithelium of both healthy control and dysplasia samples. In the lamina propria, PD‐L1 was expressed mainly in dysplastic samples and only rarely in controls.…”
Section: Discussioncontrasting
confidence: 92%
“…On the other hand, IDO1 expression in the lamina propria was enhanced with increase in dysplasia grade, which may be caused by associated inflammation and the production of pro-inflammatory cytokines. 24 In contrast to the expression of PD-L1 in cancer cells of oral squamous cell carcinoma, [25][26][27] in our study, PD-L1 was negative in the oral epithelium of both healthy control and dysplasia samples. In the lamina propria, PD-L1 was expressed mainly in dysplastic samples and only rarely in controls.…”
Section: Discussioncontrasting
confidence: 83%
“…Thirteen different studies assessed various subsets of T cells 23,28,29,34,40,[44][45][46][47][48][49][50][51] (Table 3). High numbers of tumourinfiltrating CD3+ T cells (pan T cell marker), CD4+ T cells (T helper (Th) cell marker) or CD8+ T cells (T cytotoxic (Tcyt) marker) were usually associated with somewhat longer survival, whereas high numbers of forkhead box P3 (FOXP3)+ T-regulatory cells showed significant association with decreased survival in two of the five studies addressing this cell type.…”
Section: T Cells B Cells DC and Mast Cells Lack Evidence Of Prognosmentioning
confidence: 99%
“…Similarly, Chen et al found that patients with both tumour necrosis and PD‐L1 overexpression had a worse OS (Chen, Wu, et al, ). However, six studies failed to find a relationship between OS or tumour‐associated death and PD‐L1 positivity (Cho et al, ; Kouketsu et al, ; Lin et al, ; Mattox et al, ; Satgunaseelan et al, ; Troeltzsch et al, ). Furthermore, Ahn et al found a better prognosis in OSCC with both PD‐L1 overexpression and high miR‐197 levels (Ahn et al, ).…”
Section: Clinical Implications Of Pd‐l1 Expression In Osccmentioning
confidence: 99%